2005
DOI: 10.1159/000087927
|View full text |Cite
|
Sign up to set email alerts
|

<i>APOE</i> Genotype and Serum Cholesterol in Predicting Risk for Early Death from Ischemic Stroke in Men and Women

Abstract: Background: We recently discovered that APOE ε3/ε4 genotype in men and APOE ε2/ε3 genotype in women are associated with increased risk of death from ischemic stroke (IS). One of the main physiological roles of apolipoprotein E is participation in cholesterol metabolism. A significant association of low serum cholesterol level with increased risk of death from stroke was documented. So, we aimed to establish if an association exists between APOE genotype, serum cholesterol and 1-month mortality in IS. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…In one study, no association was observed (20), and in the other, a trend toward survival benefit associated with an APOE ε4 allele (18) was documented. In a previous study we documented a significant, gender‐dependent effect of APOE ε3/ε4 genotype on increased risk of early death after the IS (11). In this study we document a significant, men‐specific, association of the E4 genotype with greater neurological deficit on admission, and with increased risk of death within the period up to 1 year after the IS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, no association was observed (20), and in the other, a trend toward survival benefit associated with an APOE ε4 allele (18) was documented. In a previous study we documented a significant, gender‐dependent effect of APOE ε3/ε4 genotype on increased risk of early death after the IS (11). In this study we document a significant, men‐specific, association of the E4 genotype with greater neurological deficit on admission, and with increased risk of death within the period up to 1 year after the IS.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous reports suggested that the total serum cholesterol is an important factor which determines mortality in stroke (44, 45). However, our previous analysis failed to confirm that lipid influences were responsible for the gender‐dependent differences in APOE genotype effects on 1‐month stroke mortality (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the APOE ε4 allele is associated with oxidative stress, microglia invasion, inflammation and an increased risk of premature atherosclerosis, which can be at least partially responsible for the increased risk of dementia and AD in ε4 allele carriers. Comparing to ApoE ε3, the ApoE ε4 isoform is more susceptible to proteolysis, leading to the accumulation of reactive fragments of ApoE ε4 in the cytosol, which results in cytoskeleton damage and neurodegeneration [8,9]. Teng et al [10] demonstrated that low plasma ApoE levels are significantly correlated with a smaller hippocampal size in patients with normal recognition or cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%